Improving Chemical Properties of Inceptisol Media Applied with Calcite and Kiserite and its Effect on Yield and Mineral Content of Moringa Leaves (Moringa oleifera Lam.) - Yunihadi Indra Rahadi; Hapsoh Hapsoh; Wawan Wawan (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2023)
This research is about the improvement of the chemical properties of Inceptisol media applied by Calcite and Kiserite and its effect on yield and mineral content of Moringa leaves (Moringa oleifera Lam.) was carried out to consider the importance of growth and productivity of Moringa plants on Inceptisol soils with high leaf Mg levels. This study aims to determine the effect of interaction and the main effect of Calcite and Kiserite treatment on improving the chemical properties of Inceptisol media, increasing the yield and mineral content of Moringa leaves. The research was conducted at Karen Nisrina Agro, Kampar Regency, with a 4x3x3 factorial Completely Randomized Design. The first factor is Calcite with 3 dose levels, 0.0 tons ha-1., 2.11 tons ha-1 and 4.22 tons ha-1. The second factor is Kiserit with 4 levels, 0.0 tons ha-1., 0.35 tons ha-1.,0.45 tons ha-1, and 0.55 tons ha-1. Observation parameters: chemical properties of the media (pH, Ca and Mg), leaf yield and stover, and leaf mineral content (Ca and Mg). Observational data were analyzed using analysis of variance at 5% significance level, followed by Duncan's multiple distance test at 5% significance level. On the chemical properties of the soil, the interaction of giving Calcite and Kiserite occurred at pH and Ca media. Calcite increases the pH and Ca media. Kieserite increases Mg and decreases Ca media. The application of Calcite and Kiserite significantly increased the yield of leaves and stover, but there was no interaction between them. For leaf mineral content, the interaction of giving Calcite and Kiserite was found in the Ca content of the leaves. Calcite and Kiserite application had no significant effect on the Ca and Mg levels of the leaves.